Conceptions of disability and desert in the South African welfare state: The case of disability grant assessment - Kelly, Gabrielle Gita (Department of Sociology, 2017)
Disability is a universally difficult concept to define and assess for social assistance and social insurance purposes. The ways in which access to disability welfare rights are defined and allocated remain especially neglected in the Global South. This thesis examines the administration of the disability grant (DG) in South Africa, where unusually generous disability benefits exist alongside very high levels of unemployment and poverty. It focuses on the role of doctors, who must confirm that applicants for the DG are disabled, serving as gatekeepers, and thus as 'street level bureaucrats' within the South African Social Security Agency (SASSA). Observations of doctor-claimant interactions in clinics and hospitals showed that disability assessments are sites of contestation between doctors, claimants and the state over how social security rights should be allocated. Doctors struggled to balance their roles and obligations as medical professionals, gatekeepers and moral agents, in a context where issues of employability and disability are hard to separate. In the face of heavy workloads and significant pressure from claimants to recommend grants, doctors employed coping strategies that distanced and objectified patients. Despite efforts by SASSA to curb their discretion, doctors inserted their own subjective understandings of disability and deservingness into the assessment process as they interpreted and applied DG policy in their interactions with claimants - bending the rules for people they thought were 'deserving' and rigidly applying the rules in 'undeserving' cases. Variation in doctors' decision-making reflects different ways of framing disability cases. The interpretive schemas that doctors used to organise and make sense of cases were shaped by their social background and dispositions, work environment, professional and personal norms and values, and ideas about distributive justice. Framing is also an interactive process and was influenced by claimants, who brought their own agency to bear on the assessment. The concept of framing contributes to street-level bureaucracy theory by capturing the pluralism of norms and ideas that ground street-level actions, whilst allowing us to observe and explain patterns emerging in street-level decisions. It is also useful in examining the relationship and potential conflicts between professional expertise, social norms and values, and bureaucratic rules. The study also shows the need for scholars of street-level bureaucracy to consider the influence of citizen agency on policy implementation. The challenges and pressures doctors faced in categorising disability, combined with patients' misunderstanding of and resistance to these categories and related demands to be included in the system, demonstrate significant gaps in the design and application of social security and poverty alleviation policy in South Africa.